AN ANALYSIS OF CODE MIXING AND CODE SWITCHING IN “THE IMPORTANCE OF LOVE IN LIFE” PODCAST ON CXO MEDIA CHANNEL - Dewi, Novi Rina; Dila Selviana (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
This aims to find the types of code mixing and code switching contained in the speech Putri Tanjung as presenter in Ngobrol Sore Semaunya and Maudy Ayunda as a celebrity guest. The steps taken in completing this thesis was watching Youtube, downloading video, then listening to speech in video repeatedly and writing it into a script required as data, then data were analyzed with descriptive qualitative method. Author obtained 172 data from utterances of Putri Tanjung and Maudy Ayunda then focused on three types of code mixing, as insertion, alternation and congruents lexicalization and three type of Code switching, namely tag switching, intra-sentential and inter-sentential code switching. The results showed that there are 103 data of code mixing which 86 data is insertion code mixing (83,5%) with detail of insertion; 64 is word insertion, 38 phrase insertion, 3 clause insertion, 17 hybrid insertion, 4 idiom insertion, and 8 repetition insertion, then 9 data is alternation code mixing (8,7%) and 8 data is congruent lexicalization code mixing (7,8%). Then the next results found 69 data of code switching. Percentage showed14 data is tag switching (20,3%), 48 data is intra-sentential code switching (69,6%) and 7 data is inter-sentential code switching (10,1%)